Water quality change and pollution source accounting of Licun River under long-term governance - Zhang, Minghui; Wang, Lin; Mu, Chunxia; Huang, Xuda (Scientific reports, 2022)
Urbanization and human activities have exerted a tremendous adverse influence on the water quality of the Licun River, Qingdao, China. In order to restore the water quality, a succession of measures have been carried out since 1996, mainly encompassing flood controlling, sewage intercepting and watercourse greening (before 2007), watercourse and point source control based on administrative region (2008–2017), as well as the comprehensive governance based on river basin (after 2018). In 2019, the amount of discharged industrial wastewater, chemical oxygen demand, and ammonia nitrogen decreased by 53.91%, 87.75% and 89.88%, respectively, compared with 2000. Such results indicate that continuous governance has achieved a quantitative effect, and that industrial discharge is not the main pollution source. In the present work, the Spearman rank correlation coefficient and river comprehensive pollution index methods were used to analyze the change trend of main pollutants. The water quality was improved continuously, and the reduction of total phosphorus and ammonia nitrogen was the key to upgrading water quality. Afterward, the emission of pollution sources was accounted for from viewpoints of the point source, non-point source and sludge. Finally, suggestions were put forward to improve the water quality of the Licun River and provide some reference for the urban river management in northern China.